Role of gravity waves in the forcing of quasi two‐day waves in the mesosphere: An observational study. Issue 9 (7th May 2013) - Ern, M.; Preusse, P.; Kalisch, S.; Kaufmann, M.; Riese, M.
Abstract: [1] Amplitudes of quasi two‐day waves (QTDWs) are derived from temperature observations of the High Resolution Dynamics Limb Sounder and Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) satellite instruments. In particular, a global climatology of QTDW amplitudes is derived from 10 years of SABER data, covering the mesosphere and lower thermosphere. This climatology is compared with geostrophic winds and climatologies of gravity wave (GW) momentum flux and GW drag absolute values derived from the same data set. We find that QTDWs are forced shortly after the maximum of the mesospheric summertime zonal wind jet in regions of jet instability where the meridional gradient of quasi‐geostrophic zonal mean potential vorticity is strongly negative. The jet instability regions are closely linked to enhanced GW drag that likely seeds those instabilities by decelerating the jet and causing the jet curvature responsible for the negative potential vorticity gradient. The vertical phase structure and the Eliassen‐Palm flux of the QTDWs are derived from SABER data and investigated. It is shown that QTDWs propagate upward starting from the jet instability regions. They exert eastward drag in the jet core, and strong westward drag at higher altitudes. Strikingly, the QTDWs are forced in regions where the global distribution of GWs exhibits a characteristic longitudinal structure caused by the GW source patterns in the summer hemisphere. This longitudinal structure might play an important role in the forcing of QTDWs; however, no clear link has been found to the observed QTDW zonal wavenumbers. Key Points: Observations of two‐day waves, gravity waves, and zonal winds are compared Two‐day waves are forced by summertime jet instabilities seeded by gravity waves EP fluxes and flux divergence of two‐day waves are derived from observations